Pengaruh Variasi Kecepatan Putaran Benda Kerja Dan Kedalaman Pemakanan Terhadap Kekarasan Permukaan Proses Gerinda Silinderis Dengan Center Pada Baja Aisi 4140 - Novry Harryadi; Dodi Sofyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Cylindrical grinding is a fundamental process in the final machining a component that requires a smooth surface roughness and precision tolerances. Cylindrical grinding processparameter variations, among others, the speed of rotation of the workpiece and the depth of cuts. This study used three variations of round rotation workpieces are low speed (83 rpm),medium speed (194 rpm) and high speed (304 rpm). Likewise with varying depth of cut is 0.005 mm, 0.010 mm, 0.015 mm. The average value of surface roughness of AISI 4140 steelcylindrical grinding tolerances based on the value of the average surface roughness / Ra are as follows : Class N7 roughness , Ra 1.6 , Tolerance ( m) ( + 50 % and - 25 % ) is 1.2 to 2.4 , asample length of 0.8 mm. The level of the average surface roughness according to the work cylindrical grinding results Steel AISI 4140 are as follows: Working Process is finishing, Hose ( N ) N4 - N8 , Ra 0.1 to 3.2. Parameters workpiece rotation speed and depth of cut for surface roughness cylindrical grinding process AISI 4140 steel workpiece is rotating speed194 rpm and 0,010 mm depth of cuts .Keywords: Cylindrical Grinding, Rotation Speed, Depth of Cuts, Surface Roughness.